2019
DOI: 10.1007/s13181-019-00697-z
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse Effects of Physostigmine

Abstract: Introduction Physostigmine is a tertiary amine carbamate acetylcholinesterase inhibitor. Its ability to cross the blood-brain barrier makes it an effective antidote to reverse anticholinergic delirium. Physostigmine is underutilized following the publication of patients with sudden cardiac arrest after physostigmine administration in patients with tricyclic antidepressant (TCA) overdoses. We completed a narrative literature review to identify reported adverse effects associated with physostigmine administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 55 publications
2
17
0
4
Order By: Relevance
“…A 10-year retrospective cohort study was conducted in 2018 showed physostigmine to have a good safety profile with the ability to improve, and in some cases, resolved anticholinergic delirium when administered in doses less than 2mg [4]. These finding are further supported by a meta-analysis published in 2019 which analyzed data of 161 papers, and 2,299 patients concluding that physostigmine was a safe antidote to treat an anticholinergic overdose [5].…”
Section: Safety Profilementioning
confidence: 91%
“…A 10-year retrospective cohort study was conducted in 2018 showed physostigmine to have a good safety profile with the ability to improve, and in some cases, resolved anticholinergic delirium when administered in doses less than 2mg [4]. These finding are further supported by a meta-analysis published in 2019 which analyzed data of 161 papers, and 2,299 patients concluding that physostigmine was a safe antidote to treat an anticholinergic overdose [5].…”
Section: Safety Profilementioning
confidence: 91%
“…ChEI was first investigated for the treatment of AD however discontinued for multiple adverse effects (96). Ambenonium chloride AChE inhibitor and down-regulates a6b2 -nAChR mediated dopamine release.…”
Section: Rivastigminementioning
confidence: 99%
“…This drug has a methylcarbamate substituent and basic groups that bind to the anionic site of AChE. The transfer of the carbamoyl group to the serine hydroxyl group of the stearic site of the enzyme is the same as observed for ACh, but the carbamylated enzyme hydrolyzes much more slowly, recovering its enzymatic activity after several minutes, instead of microseconds (Andrade and Gondal 2020;Arens and Kearney 2019). The slow recovery of the carbamylated enzyme implies that it displays a rather prolonged effect, increasing cholinergic transmission.…”
Section: In Vivo Studies: Object Recognition Test (Ort)mentioning
confidence: 99%